An analysis on the relations between religious scholars and secular leaders as described in traditional Malay texts - Abdul Jalil, Mohd. Noh (s.n, 2012)
Religion has always played an important role in the political milieu of the Malay Archipelago since the establishment of the first known Malay kingdom almost two thousand years ago. Different roles have been entrusted to the religious authorities by the Malay rulers. During the period of Indian cultural and religious dominance, religious scholars had a special position at the court and played a significant role in maintaining the legitimacy of the king. This paper looks how, after the spread of Islam to the Malay Archipelago relationship between religious scholars and secular leaders changed drastically. Religious scholars maintained a less direct relationship with secular leaders compared to the role of the Brahmin of the devaraja